Sensory Evaluation of Fish Flavoured Spicy Tamarind Paste Prepared from Different Type of Chilies - Zainol, Nur Athirah; Muhammad, Norhayati (Enhanced Knowledge in Sciences and Technology, 2023)
Fish flavored spicy tamarind dish is one of the traditional foods in Malaysia, especially in Johor and Melaka. The main ingredient in the production of spicy tamarind dish is chili. Each chili has a different amount of capsaicin. In this study, the amount of capsaicin in each chili used has been identified. The capsaicin value for fresh chillies is 289.74±5.15, non-spicy dried chillies 311.99±6.08 and spicy dried chillies 494.41±20.46. After that, the use of fresh chilies and dried chilies in the production of spicy tamarind paste can affect the attributes in the sensory test. This is because some places use fresh chilies and others use dried chilies. In this study, this sensory evaluation test can determine the difference in using fresh chilies and dried chilies as variable ingredients in the production of fish flavored spicy tamarind paste. This sensory evaluation test was conducted using 14 formulations produced using Design Expert Software. After that, the analyzed data has optimized a new formulation which is 15% of spicy dried chili and 13% of non-spicy dried chili. The differences between predicted and experimental values ​​for texture, color, spiciness and overall acceptance parameters were 2.08%, 2.29%, 2.76, and 2.54% for process validation.